Pengelompokan Data Warga Dalam Pengurusan Surat Keterangan Berdasarkan Tujuan Dengan Menggunakan Metode Clustering: Desa Perkebunan Bandar Telu - Dwi Fitri Rahayu; Akim Manoar Hara Pardede; Suci Ramadani (Pusat Riset dan Inovasi Nasional, 2025)
Perkebunan Bandar Telu Village, located in Salapian Subdistrict, Langkat Regency, is an area with high administrative activity, particularly regarding requests for various types of official letters such as business certificates, poverty certificates, and domicile certificates. Currently, the request documentation process is handled manually using physical record books, which causes the collected data to remain underutilized and merely archived. This study aims to cluster citizen data based on the purpose of the certificate requests to support informed decision-making by the village administration. The method applied is data mining using the K-Means clustering algorithm, and data processing was carried out using Matlab software. The results identified three primary clusters: Cluster 1 consists of citizens aged 46–59, mainly housewives, requesting poverty certificates (192 data points); Cluster 2 includes citizens aged 17–25, primarily students, requesting marriage certificates (201 data points); and Cluster 3 consists of citizens aged 26–45, also mostly housewives, requesting business licenses (217 data points). These findings provide actionable insights that can be used to prioritize public services, design targeted policies, and improve administrative efficiency in Perkebunan Bandar Telu Village.